Proton versus conventional radiotherapy for pediatric salivary gland tumors: Acute toxicity and dosimetric characteristics. Issue 2 (August 2015) - Grant, Stephen R.; Grosshans, David R.; Bilton, Stephen D.; Garcia, John A.; Amin, Mayank; Chambers, Mark S.; McGovern, Susan L.; McAleer, Mary F.; Morrison, William H.; Huh, Winston W.; Kupferman, Michael E.; Mahajan, Anita
Abstract: Purpose: We evaluated acute toxicity profiles and dosimetric data for children with salivary gland tumors treated with adjuvant photon/electron-based radiation therapy (X/E RT) or proton therapy (PRT). Methods and materials: We identified 24 patients who had received adjuvant radiotherapy for salivary gland tumors. Data were extracted from the medical records and the treatment planning systems. Toxicity was scored according to the Common Terminology Criteria for Adverse Effects 4.0. Results: Eleven patients received X/E RT and 13 PRT, with a median prescribed dose of 60 Gy in each group. In the X/E RT group, 54% of patients developed acute grade II/III dermatitis, 27% grade II/III dysphagia, and 91% grade II/III mucositis, and the median weight loss was 5.3% with one patient requiring feeding tube placement. In the PRT group, 53% had acute grade II/III dermatitis, 0% grade II/III dysphagia, and 46% grade II/III mucositis, with a median weight gain of 1.2%. Additionally, PRT was associated with lower mean doses to several normal surrounding midline and contralateral structures. Conclusion: In this retrospective study of pediatric salivary tumors, PRT was associated with a favorable acute toxicity and dosimetric profile. Continued follow-up is needed to identify long-term toxicity and survival data.